Compact Guide to Web Page Creation and Design / Second Edition - Ericksen Linda (Prentice Hall, 2001)
Overview of Web Publishing, Basic HTML, Enhancing the Home Page, Linking to Other Documents and Creating Forms, Enhancing and Evaluating a Home Page, Alphabetized List of HTML Tags and Attributes Used in This Book.